Trend Politainment dalam Pemberitaan Debat Capres Pemilihan Umum Indonesia Tahun 2024 - Kevin Reynaldi Priandika; Deniawan Tommy Chandra Wijaya (Universitas Sebelas Maret (UNS), 2024)
As the 2024 election approaches, politicians are competing to gain public attention, especially from young voters, by using the concept of politainment. However, it is not only politicians who are using politainment; the mass medias are also using it to attract public attention. This research discusses the trend of politainment in online media, specifically Kompas.com and CNNIndonesia.com, in their coverage leading up to the 2024 presidential election. The researcher sampled 25 news articles about the first presidential debate from Kompas.com and CNNIndonesia.com, covering the period from December 12 to December 22, 2023. This research is qualitative and uses Robert Entman's framing analysis model, which consists of four steps: define problems, diagnose causes, make moral judgments, and recommend treatments. The 25 news articles were divided into four groups based on the type of politainment discussed: character, fashion, family, and expressions/gestures. The analysis revealed that Kompas.com and CNNIndonesia.com predominantly used character-based politainment and reported positively on Prabowo, Anies, and Major Teddy, while Gibran was reported with a more negative tone. Fashion- based politainment was used by both Kompas.com and CNNIndonesia.com to report on Ganjar in a positive light. Kompas.com published more articles than CNNIndonesia.com on family-based politainment, framing the relationship between Ganjar and Mahfud with their respective sons positively. Lastly, both Kompas.com and CNNIndonesia.com covered expressions and gestures politainment positively for Prabowo and Gibran. Character issues were generally conveyed using metaphorical language, while fashion, family, and expressions/gestures issues tended not to use any specific stylistic language.